Representation of Ethnic Symbol as an Emergency Status in the Movie “Tunanganku Mautku”: Semiotics Analysis - Wali, Abdul; Ibtisam; Sulistyowati; Firmonasari, Aprillia (Southeast Asian Language and Literature Studies, 2024)
A movie that portrays the traditions of its own region is more effective in conveying moral messages based on events that have occurred. Therefore, this research examines the representation of a short movie originating from the Madurese community titled "Tunanganku Mautku," which represents the occurrence of the "carok" tradition with a woman as the main cause. Madura has been known for its strong tradition of arranged marriages since ancient times. Just like in this movie, the character Anshori binds his ring finger with Ulfa's through the arranged marriage arranged by their parents. However, behind this, there is a figure named Supri who first captured Ulfa's heart and told her to wait. Supri felt his dignity was being trampled on by Ulfa's family because Ulfa and Anshori were matched by Ulfa's parents on the grounds of greater wealth and family ties. Based on the results of the reading and analysis conducted by the researcher, the Madurese community has applied a normalization of emergency status with an ethnic symbol, namely "carok." Therefore, in this context, Supri is not blamed; instead, customary law holds Anshori responsible for taking a woman who is already under Supri's authority. Roland Barthes introduced the terms "signifier" and "signified," which were developed into a theory of metalanguage with two levels: denotation and connotation, and myths. This is in line with research related to the transcript text in the movie to explain the aspects or realities depicted in the movie "Tunanganku Mautku".